2019
DOI: 10.1101/729798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential detection of Entamoeba species in stool samples collected from children in District Swat, Khyber Pakhtunkhwa Pakistan

Abstract: 29Background: Amoebiasis is an intestinal disease caused by enteric protozoan called 30 Entamoeba histolytica belongs to the Genus Entamoeba. The main reason of infection is the 31 contamination of food and water due to the poor sanitation. Among Entamoeba species, 32 Entamoeba histolytica is highly pathogenic while the other species are non-pathogenic and 33 needs no medical treatment. 34Methodology: A total of 400 stool samples were collected from different areas of 35 district Swat and were process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our presents study were nearly result for Ngui et al, (2012) recorded 69.3% (52/75) by nested multiplex PCR in Malaysia . In addition, Khan et al, (2019) use PCR reaction to confirmed 72.07% (80/111) out of microscope positive samples real for the parasites in fecal specimens .…”
Section: Results Of Molecular Study Results Of Nested Multiplex Pcr (...mentioning
confidence: 99%
“…Our presents study were nearly result for Ngui et al, (2012) recorded 69.3% (52/75) by nested multiplex PCR in Malaysia . In addition, Khan et al, (2019) use PCR reaction to confirmed 72.07% (80/111) out of microscope positive samples real for the parasites in fecal specimens .…”
Section: Results Of Molecular Study Results Of Nested Multiplex Pcr (...mentioning
confidence: 99%
“…Khan et al . [ 31 ] reported a different prevalence, E. dispar had higher prevalence (57.5%) than E. histolytica (47.5%). Another study reported a prevalence of 10% with E. dispar and 5% with E. histolytica in humans [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contracting E. histolytica infections can be increased by keeping pets due to the parasite’s prevalence in animals and its spread through contamination. Therefore, it is proposed that more research should be conducted to identify and determine the genetic diversity of these parasites, as well as to determine the true pathogenicity and risk factors associated with Entamoeba species [ 31 ].…”
Section: Discussionmentioning
confidence: 99%